Life skills education : teachers' perceptions in primary school classrooms in Finland and Singapore - Tan, Sabrina (2018)
This research paints a picture of how life skills education could look like as part of the curriculum in every day school life in primary schools in Finland in Singapore through the lens of teachers. Life skills education is discussed with reference to formal structures as set by the curriculum and also through informal approaches by teachers. Previous literature on life skills was considered in arriving at the main components of life skills to be used in this study.